Review Of Juridical Registration Implementation And Transfer Of Land Or Building With Deed Land Sale In The Office Of The Samarinda City - Winarti Winarti; Rofi'atun Rofi'atun; Ngadino Ngadino (Jurnal Akta, 2019)
The purpose of this study was to: 1) analyze the implementation of transitional registration of rights to land and or building with the Sale and Purchase Agreements in the Land Office Samarinda. 2) Analyze the obstacles in the implementation of transitional registration of rights to land and or building with the Sale and Purchase Agreements in the Land Office Samarinda. 3) Know and analyze the solutions to overcome obstacles in the implementation of transitional registration of rights to land and or building with the Sale and Purchase Agreements in the Land Office SamarindaThis research is normative juridical approach, with specification of descriptive analysis. The collection of primary and secondary data obtained by interview and literature.The research results are: 1) Each transition of ownership of the land by way of sale and purchase, subsequent to the transfer of rights by PPAT local as evidenced by the deed of sale, then PPAT concerned within 7 business days from the signing of the deed shall register the transfer of property rights on the ground at the local land Office Samarinda especially by bringing in heaps of applicants required. 2) Barriers that occurs in the transition process of land rights through sale and purchase of the Land Office of Samarinda is because people are reluctant to take care of their land rights switchover due to their cost, according them high enough and only seize their working time. The Land Office step in overcoming these obstacles,Keywords: Sale and Purchase Agreements; Registration of Land; Certificate.